The Significance of the Handshake Based on Religious and Social Perspectives (Analytical Study of Yusuf al-Qardhawi and Petter L. Berger) - Ramdani, Acep Dani; Noorhidayati, Salamah; Rohandy, Fajar; Apriani, Laelati Dwina (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
A habit that exists in the community is a culture that is carried out continuously in a descending way so that it becomes an important part of people's social life. Like shaking hands is a habit that almost everyone has, regardless of ethnicity, race, religion, age, or social status. shaking hands or shaking hands becomes a symbol of the bond of a social relationship, whether business relations, friendship, kinship, and others. However, Islam as a religion that maintains benefit has a legal procedure for shaking hands with other people. Shaking hands between men and women who are not mahrams is a problem in society. some people believe in his permissibility, and others believe in his prohibition. This study aims to discuss handshakes from religious and social perspectives. This research method uses a qualitative type with secondary sources, namely books, theses, dissertations, and journals related to this research. Furthermore, this study applies content analysis as a means to examine the collected data so that conclusions can be drawn. This research results from a handshake analysis from religious and social perspectives with Yusuf al-Qardhawi’s theoretical approach and Peter L. Berger’s theory. This study concludes that there is a correlation between Yusuf al-Qardhawi’s theory of the handshake and the social construction analysis of Peter L. Berger.